1989
DOI: 10.1111/j.1432-1033.1989.tb14653.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution conformation of sialosylcerebroside (GM4) and its NeuAc(α2→3)Galβ sugar component

Abstract: The solution conformations of GM4 ganglioside [NeuAc(a2+3)Gal(Pl -+l)Cer] in (ZH3C)zS0 and its component disaccharide in 'HzO were investigated with the aid of 'H-nuclear magnetic resonance spectroscopy (nuclear Overhauser effect, analysis of coupling constants) and by energy-minimum calculations. The existence of three low-energy conformers obtained by theoretical calculations was supported by experimental findings in the case of GM4, whereas the disaccharide appears to exist as a mixture of two conformers.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…Conversely, the -2,3 linkage stays in two regions characterized by the ±gauche orientation of the   angle and by the gauche orientation of the  3 angle. It is noteworthy that the calculated conformations for the -2,6 and -2,3 linkages in complex with N1 are similar to conformers determined from NMR data [38,39] for these structural moieties. Through NMR studies it was found [38] that the disaccharide α-Neu5Ac-2,3-β-Gal exists in solution as a mixture of two conformers with glycosidic dihedral angles ( = -153º,  = -26 º) and (-85 º,120 º), where  = (C1-C2-O2-C3"), and  = (C2-O2-C3"-H3") respectively.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 54%
“…Conversely, the -2,3 linkage stays in two regions characterized by the ±gauche orientation of the   angle and by the gauche orientation of the  3 angle. It is noteworthy that the calculated conformations for the -2,6 and -2,3 linkages in complex with N1 are similar to conformers determined from NMR data [38,39] for these structural moieties. Through NMR studies it was found [38] that the disaccharide α-Neu5Ac-2,3-β-Gal exists in solution as a mixture of two conformers with glycosidic dihedral angles ( = -153º,  = -26 º) and (-85 º,120 º), where  = (C1-C2-O2-C3"), and  = (C2-O2-C3"-H3") respectively.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 54%
“…22 The NMR studies are coupled with computations to provide values for the /-and w-angles that are consistent with the NMR spectra. Eight NMR values yielded a /-and w-values of 243.58 6 14.88 and 2139.38 6 17.88, [37][38][39][40][42][43][44] corresponding to the most populated MD conformation. One NMR study yielded a values of 358 and 21088, 43 whose /-value corresponds to the less populated MD family.…”
Section: 36mentioning
confidence: 99%
“…3-Gal, it was inferred that f can take up all the three staggered conformations whereas c is restricted to the 2ac region [32,66]. However, one-dimensional steady-state NOE measurements indicated that the disaccharide exists as a mixture of conformers with f in the anti and 2sc conformations [67]. The conformation of the a2 !…”
Section: A 2 ! 3-linkagementioning
confidence: 99%